2010
DOI: 10.1007/s11419-010-0106-x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of simultaneous analysis of tetrodotoxin, 4-epitetrodotoxin, 4,9-anhydrotetrodotoxin, and 5,6,11-trideoxytetrodotoxin by hydrophilic interaction liquid chromatography–tandem mass spectrometry

Abstract: Recently, liquid chromatography-mass spectrometry (LC-MS) has been recognized as a useful method to analyze tetrodotoxin (TTX), the primary toxin for puffer fish poisoning. TTX usually exists with its chemically interchangeable analogs, such as 4-epiTTX and 4, 9-anhydroTTX. TTX and 4-epiTTX have the same molecular weight and the same fragmentation pattern by tandem mass spectrometry (MS-MS). In this study, we optimized conditions for hydrophilic interaction liquid chromatography (HILC)-MS-MS to quantitate TTX,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 14 publications
0
45
0
Order By: Relevance
“…In this mode, both the Q1 scan mass chromatograms and the fragment ion spectra from the specific precursor ions ([M + H] + m/z 288.1190 ± 0.1 for dideoxyTTX) are simultaneously obtained. In this experiment, TTXs were separated in HILIC mode as we reported previously [29,41,43,44]. The extract ion chromatograms (EICs) for [M + H] + of these dideoxy analogs are shown in Figure 2A, their fragment ion spectra with the high resolution masses and predicted molecular formulas are shown in Figure 2B, and the fragment ion spectra of TTX and 5,6,11-trideoxyTTX are also shown in Figure 3 for comparison.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this mode, both the Q1 scan mass chromatograms and the fragment ion spectra from the specific precursor ions ([M + H] + m/z 288.1190 ± 0.1 for dideoxyTTX) are simultaneously obtained. In this experiment, TTXs were separated in HILIC mode as we reported previously [29,41,43,44]. The extract ion chromatograms (EICs) for [M + H] + of these dideoxy analogs are shown in Figure 2A, their fragment ion spectra with the high resolution masses and predicted molecular formulas are shown in Figure 2B, and the fragment ion spectra of TTX and 5,6,11-trideoxyTTX are also shown in Figure 3 for comparison.…”
Section: Resultsmentioning
confidence: 99%
“…Liquid chromatography was performed on a 2.0 i.d. × 150 mm (5 µm) TSK-GEL Amide-80 column (Tosoh, Tokyo, Japan) using 16 mM ammonium formate in water/acetonitrile/formic acid (30:70:0.002, v/v) as a mobile phase at the flow rate of 0.2 mL/min at 25 °C [44]. The liquid chromatography system was connected to a Q-TOF MS spectrometer, MicrOTOFQII (Bruker Daltonics, Bremen, Germany), equipped with an ESI source.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The typical positive ionisation provides a TTX ion of 320 ( m / z ) (McNabb et al., ). Although the main product ion for TTX is 162 ( m / z ), other TTX analogues can generate this same ion, and hence the MRM mode is commonly used to identify different analogues (Shoji et al., ; Jang et al., ; McNabb et al., , ; Yotsu‐Yamashita et al., , ).…”
Section: Assessmentmentioning
confidence: 99%
“…The quantitative ion pair m/z 320→302 is attributed to the transition [M+H] + →[M+H-H 2 O] + and the qualitative ion pair m/z 320→162 is attributed to the product ion of 2-aminohydroquinazoline in tandem MS [49]. Prior reports showed that almost all TTX analogs were associated with these two transitions in LC-MS/MS measurement [18,31,49]. Rodríguez et al and Pires et al reported possible TTX analogs [18,31] in pufferfish and + , respectively).…”
Section: Detection Of Ttx and Its Analogs In Cooked Seafoodmentioning
confidence: 99%